Formulation of Nanoemulsion Based Sungkai Leaves Extract (Peronema canescens Jack) and Cinnamon Oil (Cinnamomum Burmannii (Nees & Th Nees) Blume) as an Antioxidant and Skin Protection Factors (SPF) Agent - Agustin, Putri; Ihsan, Mahya; Lestari, Ade; Tarigan, Indra Lasmana (Departemen Kimia, 2025)
Sungkai (Peronema canescens Jack) and Cinnamon (Cinnamomum burmannii) are herbal plants which are known to have a high content of secondary metabolite compounds as a source of natural antioxidants which are able to inhibit free radical compounds in the body and convert these free radical compounds into non-radical compounds. The greater the free radical scavenger activity in the product, the better the SPF value will be. However, the use of the extract as an active substance in cosmetic dosage forms has a low pharmaceutical elegance, so the extract is formulated using the SNEDDS (Self Nano-Emulsifying Drug Delivery System) technique. Nanoemulsion able to increase the solubility of natural ingredients by eliminating variability in absorption, permeability, and the bioavailability of drugs or bioactive compounds from natural ingredient extracts by maximizing drug penetration into the body and minimizing side effects. The aim of this research is to characterize a nanoemulsion preparation from a combination of sungkai leaves extract and cinnamon in order to obtain the optimal formula for a nanoemulsion preparation as an antioxidant product and skin protection factor agent. This research began with making extracts using the maceration method using 96% ethanol solvent, followed by making nanoemulsions using the spontaneous method. The extract concentration used was 200 mg. Observation of physical properties includes centrifugation test, organoleptic test, percent transmittance, solubility, pH, emulsion type, particle size, polydispersity index, antioxidant activity, SPF value of nanoemulsion preparation and irritation test. Analysis was carried out based on descriptive test parameters. Based on the research results, nanoemulsion preparations were made with Tween 80 surfactant, PEG 400 cosurfactant, VCO oil phase, and aqua deion water phase. So that the optimum formula nanoemulsion preparation (F1) was obtained with an active substance concentration of 100 mg sungkai extract and 100 mg cinnamon extract that met the requirements as a transparent, stable, visual nanoemulsion preparation product, with a transmittance value of 98%, a skin pH range of 6.14, having emulsion type (o/w) with a nanoemulsion particle size of 35.0 nm, PI of 0.479 and has a very strong IC50 antioxidant activity of 20.29 ppm with an SPF value of 7.4 in extra protection.